Crop Production and Environmental Impacts under Organic Management with Reduced Tillage and Diversified Cropping. Issue 1 (29th January 2020) - Fernandez, Myriam R.; Zentner, Robert P.; Schellenberg, Michael P.; Aladenola, Olanike; Leeson, Julia Y.; St. Luce, Mervin; McConkey, Brian G.; Cutforth, Herb
Abstract : In the Canadian Prairies, organic agriculture has traditionally relied on summer fallow and mechanical tillage for nutrient and pest management. More recently, there has been a substantial increase in the use of legume green manure, diversified crop rotations, and reduced tillage. The objectives of this study were to determine if diversified crop rotations and reduced tillage under organic management can maintain soil fertility and quality at adequate levels, keep weed populations at low levels, and foster healthy plants for sustainable and profitable production of annual crops. Earn 1.5 CEUs in Crop Management by reading this article and taking the quiz at https://www.certifiedcropadviser.org/education/classroom/classes/692 .